Leishmanicidal Activities of Novel Synthetic Furoxan and Benzofuroxan Derivatives - Dutra, Luiz Antonio [UNESP]; Almeida, Leticia de [UNESP]; Passalacqua, Thais G. [UNESP]; Reis, Juliana Santana [UNESP]; Torres, Fabio A. E. [UNESP]; Martinez, Isabel [UNESP]; Peccinini, Rosangela Goncalves [UNESP]; Chin, Chung Man [UNESP]; Chegaev, Konstantin; Guglielmo, Stefano; Fruttero, Roberta; Graminha, Márcia Aparecida Silva [UNESP]; et al. (Amer Soc Microbiology, 2014)
A novel series of furoxan (1,2,5-oxadiazole 2-oxide) (compounds 3, 4a and -b, 13a and -b, and 14a to -f) and benzofuroxan (benzo[c][1,2,5] oxadiazole 1-oxide) (compounds 7 and 8a to -c) derivatives were synthesized, characterized, and evaluated for in vitro activity against promastigote and intracellular amastigote forms of Leishmania amazonensis. The furoxan derivatives exhibited the ability to generate nitric oxide at different levels (7.8% to 27.4%). The benzofuroxan derivative 8a was able to increase nitrite production in medium supernatant from murine macrophages infected with L. amazonensis at 0.75 mM after 48 h. Furoxan and benzofuroxan derivatives showed remarkable leishmanicidal activity against both promastigote and intracellular amastigote forms. Compounds 8a, 14a and -b, and 14d exerted selective leishmanicidal activities superior to those of amphotericin B and pentamidine. In vitro studies at pH 5.4 reveal that compound 8a is stable until 8 h and that compound 14a behaves as a prodrug, releasing the active aldehyde 13a. These compounds have emerged as promising novel drug candidates for the treatment of leishmaniasis.